CRITERIA OF THE AVIATION NOISE ASSESSMENT FOR AERODROME ENVIRONS ZONING OF THE AIRPORTS AND PROTECTIVE MEASURES JUSTIFICATION - O. A. Kartyshev; N. I. Nikolaykin (Научный вестник МГТУ ГА, 2017)
Problems in the sphere of an adverse ecological effect assessment of aerodrome environs aviation noise are analyzed. It is noted, that there is no modern standard and methodical base for such assessment. It is shown that when planning the building, and also when developing noise-protective actions for residential areas in the zones of aviation noise increased level impact it’s most effectively to carry out acoustic zoning of areas near airports borders and flight routes. The system of transport sources noise rationing in Russia doesn't consider the established practice of its application. The aircraft of noisy types were actively taken out of service and aviation noise impact near the airports decreased, but the problem of noise protection, demands control when planning land use. Noise measurements in residential areas, near houses and inside, showed the excess of maximum allowed level values to 25-35 dBA (on equivalent value) and to 25-40 dBA (on the maximum value).As a consequence of the European states policy in the sphere of aviation noise management and of aerodrome environs zoning noise levels at the airports of Europe and their surroundings were stabilized and the sizes of noise contours were reduced. For different countries there was made the analysis of legislative bases of the implementation of the restriction requirement for residential areas and the possibility of using the territory under noise impact. For rationing theaerodrome environs noise of the airports it’s offered to take a sound equivalent level in which admissible values are ranged on three zones for the main standard criterion. The authors present acoustic measurements results in houses near the airport Vnukovo on condition of using standard two-chamber trimmable and folding windows with the ventilating valve. It is shown that the popular window designs can't provide inside noise reduction at night to the standard L Amax level = 45 dBA from the aviation source creating noise L Amax > 75 dBA; sound insulation efficiency of the used blocks is insufficient. Criteria of aviation noise assessment for zoning of the domestic airports aerodrome environs are offered.